Shift of the Branching Point of the Side‐Chain in Naphthalenediimide (NDI)‐Based Polymer for Enhanced Electron Mobility and All‐Polymer Solar Cell Performance. (6th August 2018) - You, Hoseon; Kim, Donguk; Cho, Han‐Hee; Lee, Changyeon; Chong, Sanggyu; Ahn, Nam Young; Seo, Myungeun; Kim, Jihan; Kim, Felix Sunjoo; Kim, Bumjoon J.
Abstract: The branching point of the side‐chain of naphthalenediimide (NDI)‐based conjugated polymers is systematically controlled by incorporating four different side‐chains, i.e., 2‐hexyloctyl (P(NDI1‐T)), 3‐hexylnonyl (P(NDI2‐T)), 4‐hexyldecyl (P(NDI3‐T)), and 5‐hexylundecyl (P(NDI4‐T)). When the branching point is located farther away from the conjugated backbones, steric hindrance around the backbone is relaxed and the intermolecular interactions between the polymer chains become stronger, which promotes the formation of crystalline structures in thin film state. In particular, thermally annealed films of P(NDI3‐T) and P(NDI4‐T), which have branching points far away from the backbone, possess more‐developed bimodal structure along both the face‐on and edge‐on orientations. Consequently, the field‐effect electron mobilities of P(NDI m ‐T) polymers are monotonically increased from 0.03 cm 2 V −1 s −1 in P(NDI1‐T) to 0.22 cm 2 V −1 s −1 in P(NDI4‐T), accompanied by reduced activation energy and contact resistance of the thin films. In addition, when the series of P(NDI m ‐T) polymers is applied in all‐polymer solar cells (all‐PSCs) as electron acceptor, remarkably high‐power conversion efficiency of 7.1% is achieved along with enhanced current density in P(NDI3‐T)‐based all‐PSCs, which is mainly attributed to red‐shifted light absorption and enhanced electron‐transporting ability. Abstract : The branching point of side chain in naphthalenediimide (NDI)‐based polymers is systematically controlled. As the branching point shifts away from the backbone, the well‐ordered intermolecular assembly with bimodal orientations evolves, resulting in a red‐shifted absorption and a higher electron mobility. All‐polymer solar cells (all‐PSCs) benefit from these changes by achieving a power conversion efficiency of 7.1%.